Fetus as a Subject in Culture: A Contextual Study of Pregnancy Practices and Beliefs in Indonesia - Mujur, Maximus; Mulyana, Deddy; Dida, Susanne; Mose, Johanes Cornelius (Journal of Cultural Analysis and Social Change, 2025)
This article analyzes the position of the fetus as a subject within various Indonesian cultural contexts, highlighting how communities interpret fetal existence beyond its biological dimensions. In many Nusantara traditions, the fetus is regarded as a being that possesses social, moral, and spiritual status from an early stage, and its presence is acknowledged and honored through diverse cultural practices. Using a comparative ethnographic approach, this article examines how communities in Java, Sunda, Bali, Minangkabau, East Nusa Tenggara, and Papua understand the existence of the fetus and construct ritual communication patterns that connect the mother with the unborn child. In Javanese and Sundanese contexts, for example, rituals such as mitoni and tingkeban are not merely markers of gestational age but also ceremonial acts of welcoming a new subject believed to have already entered the familial sphere. In Bali, the concepts of bhuta kala and cosmic harmony situate the fetus within a spiritual structure that requires balance between the mother’s body and the natural world. Minangkabau communities view the fetus as part of the matrilineal lineage, linking its status closely to clan identity. Meanwhile, in East Nusa Tenggara—particularly within Atoni Pah Meto and Kelimutu traditions—the fetus is often treated as a person who must be protected through taboos, prayers, and symbolic safeguards. In Papua, pregnancy is understood as a relational process involving the mother, ancestors, and nature spirits who watch over the fetus’s life journey. This study demonstrates that Indonesian traditions construct a dialogical mother–fetus relationship that influences maternal emotional well-being, the quality of prenatal bonding, and cultural conceptions of the beginning of human life. Thus, the fetus is not merely positioned as “one who will become,” but as a subject already occupying social and spiritual space within the community.